Arnold's Poetic Landscapes - Roper, Alan (Johns Hopkins University Press, 2019)
Originally published in 1969. Alan Roper studies the degree to which Arnold achieved a unity of human significance and literal landscape. If landscape poetry is to rise above the level of what Roper calls "country contentments in verse," the poet cannot think and describe alternately; his thinking and describing must be a part of one another. That Matthew Arnold was aware of the difficulty in achieving the necessary unity becomes clear in his own criticism, which Roper examines along with a large and representative number of Arnold's poems. Considering the latter roughly in the order they were published-except for a fuller analysis of Empedocles on Etna, "The Scholar-Gipsy," and "Thyrsis"-Roper follows important changes in Arnold's view of the function and nature of poetry as it emerged in the poems themselves. Basic to the author's critical method is a distinction between geographical sites and poetic landscapes. Focusing on the ways that Arnold and, to a lesser extent, the Augustan and Romantic poets before him untied thought and description, Roper adds a critical dimension to Arnold scholarship. Concerned not with the development of Arnold's ideas nor with their sources in classical antiquity and the Romantic period, he considers Arnold a self-conscious poet who, though sometimes successful, became increasingly unsuccessful in his efforts to imbue a landscape with meaning for individual or social man.